Library Services Of Banten Province During The Covid-19 Pandemic - Salma Fatya Azzahra; Sukaesih -; Evi Nursanti Rukmana; Samson CMS - (Universitas Airlangga, 2021)
Physical services in several libraries had to be stopped and closed in order to prevent the transmission of the Covid-19 virus. This is done as the responsibility of the library in protecting library staff and library users. Due to the closure of library services, it becomes difficult for people to access information. This condition requires libraries to look for innovations or other alternatives to help people who need information. The purpose of this article is to determine the implementation of innovations in the service sector carried out by the Banten Provincial library during the pandemic to help people who need information. This research was conducted using descriptive qualitative methods, namely methods that utilize qualitative data and described descriptively. This article examines the innovations made by the Banten Provincial Library in the face of the Covid-19 pandemic. No direct observations were made because the library was closed and following government advice to avoid crowds. As a substitute for the direct observation method, then taking another alternative, namely conducting an interview with the Head of the Banten Provincial Library Division via the WhatsApp application. Data analysis was obtained through the results of these interviews and by reviewing journals related to library services during this pandemic. Based on the research results, it can be obtained information that the policy of the Banten Province library during this pandemic is not to provide crowd services and there is no contact between librarians and users so that services in the library have to be closed. As an alternative to discontinuing physical services, the Banten Province library is looking for new innovations, namely by optimizing digital library services implemented through the Banten Province digital library application, namely iBanten, online registration through the Online Registration System (SIPANON) application, opening website services, online book review, and webinar program.